Screening and Characterization of Novel Ulvan Degrading Lyases - Malmgren,Annika (2023)
Macroalgae are found worldwide dominating the aquatic ecosystems and representing a vast still sporadically explored resource with significant potential for mitigating climate change, constitute new food alternatives, provide sustainably fuel, and possibly be involved in new pharmaceutical discoveries. Despite limited research attention, ulvan, an irregular sulphated polysaccharide found in green algae holds an immense potential for biotechnological applications. The aim of this thesis study was therefore to screen and investigate prioritized novel ulvan lyases from both metagenome targets and gene mining of Wenyingzhuangia fucanilytica genome. A novel ulvan lyase attributed to PL40 family, termed WF-PL40-V demonstrating activity on ulvan from different Ulva species and was selected as a major target enzyme for subsequent investigation. WF-PL40-V was active in the crude cell lysate of expression host and remained soluble and active after affinity purification at high concentration with no significant aggregation observed. The protein solubility as well as lack of possible oligomerization was confirmed by analytical size-exclusion chromatography (SEC). The generated AlphaFold model of WF-PL40-V analysis allowed identification of two protein domains, the N-terminal catalytic domain followed by C-terminal substrate binding domain. Investigated enzyme demonstrated activity optimum at 35°C and pH 8.5 and slight preference to Ulva sp., fine grade ulvan in presence of 10 mM CaCl2 and 25 mM NaCl. Enzyme kinetics of WF-PL40-V resulted in a Vmax of 0.15 ± 0.1 mM min-1, KM was 0.07 ± 0.06 mM and kcat was estimated to 47 s-1. The generated product pattern by WF-PL40-V was composed of different sizes of ulvan oligosaccharides analyzed via thin-layer chromatography and preparative SEC. Noteworthy, the product pattern of the investigated enzymes varied slightly when using different substrates. The reaction products of optimal substrate were subjected for NMR analysis. Bioinformatic analysis allowed prediction of WF-PL40-V to a CAZyme gene cluster 4 along with other genes encoding putative enzymes needed for ulvan full uptake by W. fucanilytica. Independent transcription of WF-PL40-V gene was also predicted. This thesis study provided screening of putative ulvan lyases generating characterization of a novel PL40 family lyase, however, more investigation needs to be conducted to understand the complicated degradation mechanism of ulvan polysaccharides and its promising biotechnological applications.
Keywords: macroalgae; ulvan; polysaccharide lyases; CAZymes; enzyme characterization; biochemistry